HISTORY OF GANDRUNG BLAMBANGAN IN PERSPECTIVE OF BANYUWANGI CULTURE: Sejarah Perkembangan Gandrung Di Bumi Blambangan Dalam Perspektif Budaya Masyarakat Banyuwangi - Ghoziyah Ilza Rona Afcarina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2020)
This study aims to examine the history of the gandrung dance in Banyuwangi, so that the people of Banyuwangi know how the origin of the gandrung dance can be popular up to now in the community itself and outside the Banyuwangi area. The problems in this study are divided into several parts, including: the history of Gandrung dance, the meaning of Gandrung Banyuwangi, the structure of the gandrung scene, the gandrung fashion, gandrung musical instrument, and the gandrung figure